Humans, fish, spiders and bees inherited working memory and attention from their last common ancestor - Earl, Brian (Frontiers in Psychology, 2023)
All brain processes that generate behaviour, apart from reflexes, operate with information that is in an “activated” state. This activated information, which is known as working memory (WM), is generated by the effect of attentional processes on incoming information or information previously stored in short-term or long-term memory (STM or LTM). Information in WM tends to remain the focus of attention; and WM, attention and STM together enable information to be available to mental processes and the behaviours that follow on from them. WM and attention underpin all flexible mental processes, such as solving problems, making choices, preparing for opportunities or threats that could be nearby, or simply finding the way home. Neither WM nor attention are necessarily conscious, and both may have evolved long before consciousness. WM and attention, with similar properties, are possessed by humans, archerfish, and other vertebrates; jumping spiders, honey bees, and other arthropods; and members of other clades, whose last common ancestor (LCA) is believed to have lived more than 600 million years ago. It has been reported that very similar genes control the development of vertebrate and arthropod brains, and were likely inherited from their LCA. Genes that control brain development are conserved because brains generate adaptive behaviour. However, the neural processes that generate behaviour operate with the activated information in WM, so WM and attention must have existed prior to the evolution of brains. It is proposed that WM and attention are widespread amongst animal species because they are phylogenetically conserved mechanisms that are essential to all mental processing, and were inherited from the LCA of vertebrates, arthropods, and some other animal clades.